See Answer

Add Answer +20 Points

Community Answer

See all the answers with 1 Unlock

Get 4 Free Unlocks by registration

Get 4 Free Unlocks by registration

Assume (6-(5x)/(6))=u:.y=u^(-6)=f(u)u=(6-(5x)/(6))=g(x)then (dy)/(dx)=(-6)(6-(5x)/(6))^(-6-1)xx((-5)/(6))(dy)/(dx)=6xx(5)/(6)(b-(5x)/(6))^(-7)(dy)/(dx)=5(6-(5x)/(6))^(-7)(ii) y=cos(tan x)quad u=tan x{:[f|u|=cos u],[u=tan x=g(x)]:}int(dy)/(dx)=-sin(tan x)xxsec^(2)x(11)" (11) "{:[y=f(u)],[y=e^(u)],[u=-5x],[(dy)/(dx)=e^(-5x)x(-5)],[(dy)/(dx)=-5e^(-5x)]:}(v){:[y=2ln 6x],[(dy)/(dx)=2xx(1)/(6x)xx6]:}[(dy)/(dx)=(2)/(x):}" (w) "y=(sin 5theta)sqrt(theta+7)taving loganithm on both side{:[ln y ... See the full answer